Fresno County Counsel Potluck Celebrating Vickie Stoutingberg's Law School Graduation - Watkins, Howard::::::::: (1987)
Food in library: Vickie Stoutingberg, Vincent McGraw, Debbie Lucas, and Sharon St. John